2010
DOI: 10.1038/nature09610
|View full text |Cite
|
Sign up to set email alerts
|

Trapped antihydrogen

Abstract: Antimatter was first predicted in 1931, by Dirac. Work with high-energy antiparticles is now commonplace, and anti-electrons are used regularly in the medical technique of positron emission tomography scanning. Antihydrogen, the bound state of an antiproton and a positron, has been produced at low energies at CERN (the European Organization for Nuclear Research) since 2002. Antihydrogen is of interest for use in a precision test of nature's fundamental symmetries. The charge conjugation/parity/time reversal (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
285
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 314 publications
(291 citation statements)
references
References 26 publications
2
285
0
1
Order By: Relevance
“…The observation of hyperfine structure in atomic hydrogen by Rabi and co-workers 1-3 and the measurement 4 of the zero-field groundstate splitting at the level of seven parts in 10 13 are important achievements of mid-twentieth-century physics. The work that led to these achievements also provided the first evidence for the anomalous magnetic moment of the electron [5][6][7][8] , inspired Schwinger's relativistic theory of quantum electrodynamics 9,10 and gave rise to the hydrogen maser 11 , which is a critical component of modern navigation, geo-positioning and very-long-baseline interferometry systems.…”
mentioning
confidence: 99%
“…The observation of hyperfine structure in atomic hydrogen by Rabi and co-workers 1-3 and the measurement 4 of the zero-field groundstate splitting at the level of seven parts in 10 13 are important achievements of mid-twentieth-century physics. The work that led to these achievements also provided the first evidence for the anomalous magnetic moment of the electron [5][6][7][8] , inspired Schwinger's relativistic theory of quantum electrodynamics 9,10 and gave rise to the hydrogen maser 11 , which is a critical component of modern navigation, geo-positioning and very-long-baseline interferometry systems.…”
mentioning
confidence: 99%
“…Historical examples of its importance include the wavelength measurements of absorption lines in the solar spectrum by Fraunhofer, the identification of transition lines by Balmer, Lyman and others, the empirical description of allowed wavelengths by Rydberg, the quantum model of Bohr, the capability of quantum electrodynamics to precisely predict transition frequencies, and modern measurements of the 1S-2S transition by Hänsch 1 to a precision of a few parts in 10 15 . Recent technological advances have allowed us to focus on antihydrogen-the antimatter equivalent of hydrogen [2][3][4] . The Standard Model predicts that there should have been equal amounts of matter and antimatter in the primordial Universe after the Big Bang, but today's Universe is observed to consist almost entirely of ordinary matter.…”
mentioning
confidence: 99%
“…Working at the Antiproton Decelerator 8 facility at CERN, we recently demonstrated magnetic confinement of cold antihydrogen atoms 3 and showed that -once trapped -these atoms end up in their ground state, where they can be held 4 for up to 1000 s. Here we use the same apparatus, modified to enable injection of microwaves into the trapping volume ( trapped, on average. The trapping field currents can be ramped down with a time constant of 9 ms, releasing trapped atoms in a well-defined time window 3 .…”
mentioning
confidence: 99%
“…The trapping field currents can be ramped down with a time constant of 9 ms, releasing trapped atoms in a well-defined time window 3 . The trapping volume is surrounded by a three-layer, 30,720-channel imaging silicon detector 9 , which can locate the spatial positions -'vertices' -of antiproton annihilations.…”
mentioning
confidence: 99%
See 1 more Smart Citation